Visible Spectrophotometric Methods for Estimation of Zopiclone from Bulk Drug and Formulation - Santosh, R.K.; Shobha, M.; Ravi, K.U.M.; Appla Raju, S. (Asian Journal of Chemistry, 2010)
Two simple extractive colorimetric methods for estimation of zopiclone, 6-(5-chloro-2-pyridyl)-6,7-dihydro-7-oxo-5H-pyrrolo- [3,4-b ]-pyrazin-5-yl-4-methyl piperazine-1-carboxylate, a non- benwdiazepine derivative which is mainly used as a hypnotic for short term management of insomnia, have been developed. The developed methods involve formation of coloured chloroform extractable complexes of drug wth bromocresol purple and bromocresol green in neutral and acidic medium. Extracted complexes showed absorption maxima at 410 om and 420 nm respectively. Results were validated statistically and were found to be reproducible.